The Oxygen–Ozone Adjunct Medical Treatment According to the Protocols from the Italian Scientific Society of Oxygen–Ozone Therapy: How Ozone Applications in the Blood Can Influence Clinical Therapy Success via the Modulation of Cell Biology and Immunity - Salvatore Chirumbolo; Luigi Valdenassi; Umberto Tirelli; Giovanni Ricevuti; Sergio Pandolfi; Francesco Vaiano; Antonio Galoforo; Fortunato Loprete; Vincenzo Simonetti; Marianna Chierchia; Debora Bellardi; Tommaso Richelmi; et al. (Biology, 2023)
Background. Ozone is an allotrope of oxygen whose use in medicine has rapidly grown in recent years. Ozonated blood allows for the use of ozone in a safe modality, as plasma and blood cells are endowed with an antioxidant system able to quench ozone’s pro-oxidant property and to elicit the Nrf2/Kwap1/ARE pathway. Methods. We present two clinical studies, a case-series (six patients) observational study adopting ozone as a major autohemotherapy and topical ozone to address infected post-surgical wounds with multi-drug resistant bacteria and an observational study (250 patients) using ozonated blood for treating knee osteoarthritis. Results. Ozonated blood via major autohemotherapy reduced the extent of infections in wounds, reduced the inflammatory biomarkers by more than 75% and improved patients’ QoL, whereas ozonated blood via minor autohemotherapy improved significantly (p < 0.001) WOMAC and Lequesne’s parameters in knee osteoarthritis. Conclusions. The models described, i.e., ozone autohemotherapy in wound antimicrobial treatment and ozonated blood in knee osteoarthrosis, following our protocols, share the outstanding ability of ozone to modulate the innate immune response and address bacterial clearance as well as inflammation and pain.